Amyotrophic Lateral Sclerosis Recent Advances and Therapeutic Challenges - Hegde, Muralidhar L. (IntechOpen, 2020)
A flurry of recent research on the role of the RNA/DNA-binding proteins TDP-43 and FUS as well as a dozen other factors (e.g., C9ORF72 and profilin) has led to a new paradigm in our understanding of the pathobiology of the motor neuron disease, Amyotrophic Lateral Sclerosis (ALS). How these factors trigger neuromuscular dysfunction is critical for developing more effective ALS therapeutics. The 'gain-of-toxicity' or 'loss-of-function' of these etiological factors is a key question. Recent studies on the imbalance in genome damage versus repair have opened avenues for potential DNA repair-based therapeutics. This book highlights emerging science in the area of ALS and discusses key approaches and mechanisms essential for developing a cure for ALS.